A retrospective analysis of clinicopathological features and outcome of secondary steroid resistant nephrotic syndrome - Qaiser, Habib; Bajeer, Irshad; Khatri, Sabeeta; Hashmi, Seema; Lanewala, Ali Asghar (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the clinico-pathological features and long-term outcome of secondary steroid-resistant nephrotic syndrome treated with steroids and calcineurin inhibitors. Method: The retrospective cohort study was conducted at the Sindh Institute of Urology and Transplant, Karachi, in June and July 2023, and comprised data from January 1, 2008, to December 31, 2020, of children aged 1-18 years who developed steroid resistance after initial sensitivity to steroids with at least 1-year of follow-up. Demographics as well as time taken to secondary steroid response were documented. Renal biopsy of all patients with secondary steroid resistance had been performed. Eventual outcomes after treatment with calcineurin inhibitors based on the degree of proteinuria and serum albumin levels were used to categorise complete remission, partial remission and no response. Kidney function, as determined by estimated glomerular filtration rate, was recorded. Data was analysed using SPSS 22. Results: Of the 1,000 patients who underwent renal biopsy for steroid resistance, 48(4.8%) had idiopathic steroid-resistant nephrotic syndrome; 32(66.7%) males, 16(33.3%) females and median age of 5 years (interquartile range: 4-7.3 years). Median age at diagnosis of nephrotic syndrome was 5 years (interquartile range: 3.6-7.3 years). The median time from nephrotic syndrome to secondary steroid-resistant nephrotic syndrome was 23 months (interquartile range: 8.75-44.5 months). Biopsy results at diagnosis showed that 27(56.3%) had minimal change disease. The mean follow-up time was 6.1±3.2 years. Of the 43(89.5%) patients who received cyclosporin for 1 year, 29(67%) obtained complete remission, 5(12%) attained partial remission and no response was seen in 9(21%) patients. Conclusion: Majority of the children had minimal change disease at the time of diagnosis of secondary steroid-resistant nephrotic syndrome. The long-term response with calcineurin inhibitors was favourable at 1 year. Key Words: Secondary steroid-resistant nephrotic syndrome, Late non-responder nephrotic syndrome, Calcineurin inhibitors, Childhood nephrotic syndrome.